Institutional Herding - Sias, Richard W. (Review of Financial Studies, 2004)
Institutional investors' demand for a security this quarter is positively correlated with their demand for the security last quarter. We attribute this to institutional investors following each other into and out of the same securities ("herding") and institutional investors following their own lag trades. Although institutional investors are "momentum" traders, little of their herding results from momentum trading. Moreover, institutional demand is more strongly related to lag institutional demand than lag returns. Results are most consistent with the hypothesis that institutions herd as a result of inferring information from each other's trades. Copyright 2004, Oxford University Press.